Application Of Asthma Exercise To Reduce Reccurence In Asthma Patients at Simpang Kawat Public Health Center Jambi City - Fajar, Muhammad; Suryati, Suryati; Oktaria, Rina; Irawan, Yeyen Gustina (Program Studi Keperawatan Universitas Jambi, 2025)
Asthma is a chronic respiratory disease that is a global health problem and affects 1-18% of the population in several countries. Asthma exercises, to increase muscle capacity related to respiratory mechanisms, increase capacity and efficiency in the respiratory process. This study aims to determine the frequency of recurrence in asthma patients at the Simpang Kawat Community Health Center, Jambi City. This research method is descriptive with a case study method. The number of subjects was one asthma patient using an asthma exercise observation sheet during which the asthma exercise was carried out for 3 meetings with asthma exercise lasting 30 minutes. After doing asthma exercises, the respondent had a recurrence of asthma once a week and after doing asthma exercises the client did not experience an asthma recurrence in the last 1 week. Asthma exercise training for 3 times can reduce the frequency of asthma recurrence in the last 1 week.